TECHNICAL ASSISTANCE AND RURAL EXTENSION IN THE BRAZIL WITHOUT POVERTY PROGRAM. A REPORT ON THE EXPERIENCE OF THE MUNICIPALITY OF CAXIAS/MA - Teixeira, Ney Jefferson Pereira; Fedrigo , Laerte (Seven Editora, 2024)
The present study intends to contribute to the production of knowledge about PATER in the PBSM from the report of the experience of the Municipality of Caxias/MA.  The first chapter analyzes the process of expansion of Rural Extension in Brazil, the main institutional changes that have occurred over the last four decades, the process of social mobilization that enabled the formulation of a new proposal for Rural Extension, as well as the conceptual bases that support the new PNATER for family farmers from the implementation of PBSM and PFAPR. The second chapter addresses the socioeconomic characteristics of the benefited families, the guidelines and objectives of the implementation and execution of the PATER, the structures of coordination, execution and social participation and the activities carried out in the proposed period. In the third chapter, the results of the Program are evaluated, according to the view of the technicians of the executing entity and the benefited families in the Municipality of Caxias/MA. The PATER, associated with a set of public policies, connected by it, has the power to lead families to the reduction of significant dimensions of poverty by overcoming indicators of deprivation, as evidenced. When outlining the visible limits of this public policy to lead the families involved to overcome the conditions that generate extreme poverty, it is necessary to consider its achievements in just two and a half years of execution and its potential for qualification in the face of the demand for continuity and deepening.DOI: https://doi.org/10.56238/sevened2024.037-078